Genomic copy number variation association study in Caucasian patients with nonsyndromic cryptorchidism. Issue 1 (December 2016) - Wang, Yanping; Li, Jin; Kolon, Thomas; Olivant Fisher, Alicia; Figueroa, T.; BaniHani, Ahmad; Hagerty, Jennifer; Gonzalez, Ricardo; Noh, Paul; Chiavacci, Rosetta; Harden, Kisha; Abrams, Debra; et al.
Abstract Background Copy number variation (CNV) is a potential contributing factor to many genetic diseases. Here we investigated the potential association of CNV with nonsyndromic cryptorchidism, the most common male congenital genitourinary defect, in a Caucasian population. Methods Genome wide genotyping were performed in 559 cases and 1772 controls (Group 1) using Illumina HumanHap550 v1, HumanHap550 v3 or Human610-Quad platforms and in 353 cases and 1149 controls (Group 2) using the Illumina Human OmniExpress 12v1 or Human OmniExpress 12v1-1. Signal intensity data including log R ratio (LRR) and B allele frequency (BAF) for each single nucleotide polymorphism (SNP) were used for CNV detection using PennCNV software. After sample quality control, gene- and CNV-based association tests were performed using cleaned data from Group 1 (493 cases and 1586 controls) and Group 2 (307 cases and 1102 controls) using ParseCNV software. Meta-analysis was performed using gene-based test results as input to identify significant genes, and CNVs in or around significant genes were identified in CNV-based association test results. Called CNVs passing quality control and signal intensity visualization examination were considered for validation using TaqMan CNV assays and QuantStudio® 3D Digital PCR System. Results The meta-analysis identified 373 genome wide significant (p < 5X10−4 ) genes/loci including 49 genes/loci with deletions and 324 with duplications. Among them, 17 genes with deletion and 1 gene with duplication were identified in CNV-based association results in both Group 1 and Group 2. Only 2 genes (NUCB2 andUPF2 ) containing deletions passed CNV quality control in both groups and signal intensity visualization examination, but laboratory validation failed to verify these deletions. Conclusions Our data do not support that structural variation is a major cause of nonsyndromic cryptorchidism.